Incidence of primary bone sarcomas in Iranian population (2008-2015): A national population-based study - Adel Ebrahimpour; Mehrdad Sadighi; Amin Karimi; Amir Sabaghzadeh; Farsad Biglari; Mohammadreza Chehrassan; Mehdi Azizmohammad Looha; Meisam Jafari Kafiabadi; Mohammad Esmaeil Akbari; Amin Nokhostin-Ansari (Babol University of Medical Sciences, 2022)
Background: Epidemiological characteristics of bone sarcomas are variant in different populations, however, there is no previous study on primary bone sarcomas among Iranian population. This study aimed to evaluate the incidence, age, sex distribution, histologic type, and location of malignant bone sarcomas, based on the Iran National Cancer Registry (INCR). Methods: This was a national population-based study using INCR data from March 20, 2008, to March 20, 2015, on patients who were diagnosed with primary bone sarcomas of the appendicular (C-code:40) and axial skeleton (C-code 41), excluding skull and face bones. Primary bone sarcomas were classified according to the International Classification of Diseases for Oncology (ICD-O-3: C40-C41). Results: A total of 4112 patients (59.5% males and 40.5% females) with a mean age of 36 years were included in the study. 60.38% of patients were between 10 to 44 years old. The overall age-standardized incidence rates (ASIR) was 8.23 (males=9.67 and females=6.80) per million person-years. Osteosarcoma chondrosarcoma and Ewing sarcoma were the three main histology subtypes with the ASIR of 2.36, 1.26, and 1.08 per million person-years. Long bones of the lower limb were the most affected area, with the ASIR of 3.18 (95% CI: 3.02-3.33) per million. We found an increasing trend in the incidence of bone sarcomas in Iran from 8.59 in 2007 to 11.37 per million person-year in 2015. Conclusion: This study provided the epidemiological features of bone sarcomas, including the histological type of sarcoma, tumors' location, and patients' age and gender in the Iranian population for the first time.